The Computation of Results from Radioimmunoassays - Finney, D. J. (Methods of Information in Medicine, 1979)
The use of radioimmunoassay (RIA) as a routine aid to clinical diagnosis makes it important that procedures for estimating the potency of each test sample are good, ancl that the validity of assumptions implicit in the calculations is regularly monitored. The task is non-trivial: if a laboratory regularly conducts varied assays, with perhaps 50-500 test samples in each, even simple manual processes (graphical or arithmetical) are very time-consuming. Only by making RIA analysis a standard computer task, can it be handled satisfactorily. If a comprehensive program serves many centres, the costs of “writing can be relatively small and other benefits can be secured — reduction in numerical mistakes, thorough examination of the adequacy of fitted response curves, production of limits of error for potency estimates, ancl ease of managing files.This paper is concerned with the principles that should underlie RIA software, and with requirements in respect of input, output, ancl analytical computations. Though not a detailed specification, it is a step towards producing a good program easily moved from one computer system to another and suitable for the computer facilities now becoming available in hospitals. If a proposed new program fails to supply many of the features described below, practitioners of radioimmunoassay not themselves expert hi statistics will be unwise to accept it as sufficient for their needs. Ease of input ancl clarity of output are essential but not sufficient in themselves. A user who adopts an apparently "simple" program may be safe for much of the time, but the occasional anomalous assay may lead to unsuspecting acceptance of wholly untrustworthy numerical conclusions.
Keywords: Radioimmunoassay; Assay Validity; Non-linear Regression; Software Specification